2013
DOI: 10.1209/0295-5075/102/58005
|View full text |Cite
|
Sign up to set email alerts
|

The topological glass in ring polymers

Abstract: Systematic coarse-graining of the dynamics of entangled polymer melts: the road fromchemistry to rheology J T Padding and W J Briels -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…In these cases, the topological constraints that they generate on the configurations of the threaded neighbours (or of itself, in the case of self-threading 25 ) lead to long-lived correlations that are strong candidates for explaining the "slowing down" in the rings' dynamics observed by several groups 14,[16][17][18]70,71 . The arguments presented here, together with several previous observations 16,18,70 also support the conjecture that in the limit of very large rings, long threadings will populate the system, and may eventually lead to spontaneous topological vitrification 72 . Compelling numerical evidence 12 indeed suggest that a "topological glass" state can be achieved by randomly pinning even a small fraction of rings in dense solutions when these are long enough.…”
Section: Return Probability On a Finite-size Surfacesupporting
confidence: 86%
See 1 more Smart Citation
“…In these cases, the topological constraints that they generate on the configurations of the threaded neighbours (or of itself, in the case of self-threading 25 ) lead to long-lived correlations that are strong candidates for explaining the "slowing down" in the rings' dynamics observed by several groups 14,[16][17][18]70,71 . The arguments presented here, together with several previous observations 16,18,70 also support the conjecture that in the limit of very large rings, long threadings will populate the system, and may eventually lead to spontaneous topological vitrification 72 . Compelling numerical evidence 12 indeed suggest that a "topological glass" state can be achieved by randomly pinning even a small fraction of rings in dense solutions when these are long enough.…”
Section: Return Probability On a Finite-size Surfacesupporting
confidence: 86%
“…10). Such large threadings may eventually generate topological constraints which can leave a signature in the long-time relaxation of the rings 3,13,16,18,70,72 and allow one to gen-erate topologically frozen states by randomly pinning a small fraction of the rings 12 . In summary, I have shown that the conformations of rings in dense solutions contain local tree-like structures that are not necessarily described by the classical tightly double-folded lattice animal picture.…”
Section: Discussionmentioning
confidence: 99%
“…Here it was shown that the number of threadings scales extensively in the polymer length (or mass) and can therefore be numerous for long rings, creating a hierarchical sequence of constraints that can span the entire system. It has also been conjectured that a kinetically frozen state, or a "topological glass" (17) can emerge, because such an extensive network of constraints can eventually suppress the translational degrees of freedom of the rings. However, the molten, or highly concentrated, state does differ from that of polymers embedded in a gel and so whether a similar jamming transition occurs for long enough polymers or even whether threadings are present in the absence of a gel remain open problems and are the main questions addressed in this study.…”
mentioning
confidence: 99%
“…Are there upper and lower critical dimensions for which random coil melts lose entanglement localization at any value of N ? Is our prediction of a mesoscopic "topological glass transition" relevant to dense liquids of ring polymers and biological analogs [9,10]? More generally, if macromolecules are not ideal random walks but still interpenetrating fractals, how does the breakdown of the isotropic Rouse model and entanglement localization evolve as a function of mass fractal and spatial dimensions?…”
Section: Discussionmentioning
confidence: 99%
“…The relevant wide range of length and times scales results in distinctive viscoelastic behavior, the first principles understanding of which is a complex task. A fundamental understanding impacts diverse problems that range from plastics processing [4,5] to biophysical phenomena such as protein folding, chromosome dynamics, and cytoskeleton mechanics [6][7][8][9][10][11].…”
Section: Introduction a General Background And Entanglement Phenomentioning
confidence: 99%